La rénovation urbaine comme occasion de réduire les inégalités face à la sécurité des déplacements - Sylvanie Godillon (Territoire en Mouvement)
Recent research shows that road traffic accidents occur more often in deprived neighbourhoods than in other areas. The factors proposed are the small proportion of recreation areas, the high traffic level and the lack of safe crosswalks. Security could thus be improved by redeveloping the urban fabric. As parts of national urban renewal programs, urban projects impact on public spaces and traffic in the neighbourhoods. Are the projects managers aware of the way they influence traffic safety ?This paper focuses on the link between traffic safety and urban renewal projects, and on the issue of a possible contradiction between them.The flexibility of the local local authorities in Germany makes it useful to compare different ways of coordinating urban renewal with traffic safety. Coordination mechanisms are analyzed at two different scales : the national elaboration of guidelines, and the implementation of local projects.Two main differences can be identified. First, in Germany both traffic safety policies and urban projects aim at making the traffic bypass the neighbourhood, whereas the will to make the traffic cross neighbourhoods often prevails in France. Second,traffic safety experts in Germany play a part in the determining of urban projects, whereas they intervene at the stage of implementation in France.Urban renewal is an opportunity to integrate traffic safety issues into neighbourhoods’ redevelopment. Local actors are aware of this opportunity and ask for this process, but in France it remains difficult to understand, given that traffic safety experts have gotten involved in the management of urban renewal projects much later than in Germany.urban renewal, urban project, traffic safety, France, Germany